Matricellular Protein CCN5 Gene Transfer Ameliorates Cardiac and Skeletal Dysfunction in mdx/utrn (±) Haploinsufficient Mice by Reducing Fibrosis and Upregulating Utrophin Expression - Song, Min Ho; Yoo, Jimeen; Oh, Jae Gyun; Kook, Hyun; Park, Woo Jin; Jeong, Dongtak (Frontiers in Cardiovascular Medicine, 2022)
Duchenne muscular dystrophy (DMD) is a genetic disorder characterized by progressive muscle degeneration due to dystrophin gene mutations. Patients with DMD initially experience muscle weakness in their limbs during adolescence. With age, patients develop fatal respiratory and cardiac dysfunctions. During the later stages of the disease, severe cardiac fibrosis occurs, compromising cardiac function. Previously, our research showed that the matricellular protein CCN5 has antifibrotic properties. Therefore, we hypothesized that CCN5 gene transfer would ameliorate cardiac fibrosis and thus improve cardiac function in DMD-induced cardiomyopathy. We utilized mdx/utrn (±) haploinsufficient mice that recapitulated the DMD-disease phenotypes and used an adeno-associated virus serotype-9 viral vector for CCN5 gene transfer. We evaluated the onset of cardiac dysfunction using echocardiography and determined the experimental starting point in 13-month-old mice. Two months after CCN5 gene transfer, cardiac function was significantly enhanced, and cardiac fibrosis was ameliorated. Additionally, running performance was improved in CCN5 gene-transfected mice. Furthermore, in silico gene profiling analysis identified utrophin as a novel transcriptional target of CCN5. This was supplemented by a utrophin promoter assay and RNA-seq analysis, which confirmed that CCN5 was directly associated with utrophin expression. Our results showed that CCN5 may be a promising therapeutic molecule for DMD-induced cardiac and skeletal dysfunction.